2022
DOI: 10.1186/s40035-022-00316-y
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and Alzheimer’s disease: mutual risks and mechanisms

Abstract: Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a life-threatening disease, especially in elderly individuals and those with comorbidities. The predominant clinical manifestation of COVID-19 is respiratory dysfunction, while neurological presentations are increasingly being recognized. SARS-CoV-2 invades host cells primarily via attachment of the spike protein to the angiotensin-converting enzyme 2 (ACE2) receptor expressed on cell membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 233 publications
0
46
0
Order By: Relevance
“…Some neurological conditions have also been linked to COVID-19 severity [ 201 , 280 , 407 ]. Possible mechanisms include immunosenescence, heightened IFN responses or genetic predisposition to severe COVID-19 (OAS1, APOE ε4 allele) in Alzheimer’s disease [ 350 , 408 , 409 , 410 ], respiratory muscle rigidity and insufficient cough reflex in Parkinson’s disease [ 350 , 411 ], systemic inflammation in epilepsy (with much uncertainty) [ 362 , 412 ] and susceptibility to acute stress in cerebrovascular diseases [ 413 , 414 ]. Increased levels of chronic inflammatory mediators have been observed in several mental disorders (major depressive disorder, bipolar disorder, schizophrenia, and sleeping disorders) [ 415 ].…”
Section: Host Factorsmentioning
confidence: 99%
“…Some neurological conditions have also been linked to COVID-19 severity [ 201 , 280 , 407 ]. Possible mechanisms include immunosenescence, heightened IFN responses or genetic predisposition to severe COVID-19 (OAS1, APOE ε4 allele) in Alzheimer’s disease [ 350 , 408 , 409 , 410 ], respiratory muscle rigidity and insufficient cough reflex in Parkinson’s disease [ 350 , 411 ], systemic inflammation in epilepsy (with much uncertainty) [ 362 , 412 ] and susceptibility to acute stress in cerebrovascular diseases [ 413 , 414 ]. Increased levels of chronic inflammatory mediators have been observed in several mental disorders (major depressive disorder, bipolar disorder, schizophrenia, and sleeping disorders) [ 415 ].…”
Section: Host Factorsmentioning
confidence: 99%
“…2 ). It has been demonstrated that SARS-CoV-2 virus could enter the brain, although the routes remain controversial [ 13 , 198 ]. However, very low levels of the SARS-CoV-2 virus are detected in the brains of patients dying from COVID-19 [ 86 , 104 106 ].…”
Section: Covid-19 and Admentioning
confidence: 99%
“…This makes AD patients more predisposed to CNS infection and adverse outcomes by the SARS-CoV-2 virus. Therefore, disruption of the ACE/ACE2 balance in AD is postulated as a contributor to the infection and severity of COVID-19 [ 198 ]. Taken together, an in-depth exploration of shared pathogenic mechanisms between AD and COVID-19 is warranted in the future, which could also in turn provide new insights into the identification of biomarkers to track disease progression and treatments of AD.…”
Section: Covid-19 and Admentioning
confidence: 99%
“…In the periphery, ApoE4 was reported to be associated with an increased risk of type 2 diabetes and cardiovascular disease [8,9]. These ApoE4related diseases have all been implicated in a higher risk of COVID-19 [10][11][12]. Impotently, recent genetic and clinical studies reported the association between the ApoE4 genotype and the risk and severity of COVID-19 disease, but yielded inconsistent results [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%